Інститут амністії: його розвиток і можливі перспективи - Александров, Юрій Валер’янович (My University, 2011)
Досліджуються характеристики нової редакції Закону України “Про застосування амністії в Україні”, хід його прийняття, висловлюється погляд на подальше існування інституту амністії. The characteristics of the new version of the Law of Ukraine “On the Application of Amnesty in Ukraine” are studied, the course of its adoption is examined, and a view is expressed on the further existence of the institution of amnesty.
Keywords: амністія; amnesty; інститут амністії; amnesty institute; Україна; Ukraine